2015
DOI: 10.1080/13102818.2015.1050789
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dynamics and material transformation characteristics of nitrite denitrification in UASB

Abstract: Nitrite is known to accumulate in wastewater treatment plants and play an important role during the biological denitrogenation process. In this study, wastewater with high nitrite concentration was effectively treated, and the possible material transformation of nitrite and carbon by microorganisms is discussed herein. While inoculating pre-acclimatized floccular sludge, nitrite-denitrifying granular sludge was obtained after approximately 15 days of cultivation in a denitrifying upflow anaerobic sludge blanke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Both Zhao et al [43] and Cuervo-López et al [44] observed nitrate and nitrite degradation efficiencies of approx. 99% in UASB reactors operating with an hydraulic retention time (HRT) of 9-12 days and 2 days, respectively.…”
Section: Input Data and Parametrization For Remineralizationmentioning
confidence: 99%
“…Both Zhao et al [43] and Cuervo-López et al [44] observed nitrate and nitrite degradation efficiencies of approx. 99% in UASB reactors operating with an hydraulic retention time (HRT) of 9-12 days and 2 days, respectively.…”
Section: Input Data and Parametrization For Remineralizationmentioning
confidence: 99%
“…Both Zhao et al (2015) and Cuervo-López et al (1999) observed nitrate and nitrite degradation efficiencies of approx. 99% in UASB reactors operating with an hydraulic retention time (HRT) of 9-12 days and 2 days, respectively.…”
Section: Input Data and Parametrization For Remineralizationmentioning
confidence: 99%